Constructed wetlands for polishing oil and gas produced water releases. Issue 12 (1st November 2021) - McLaughlin, Molly C.; McDevitt, Bonnie; Miller, Hannah; Amundson, Kaela K.; Wilkins, Michael J.; Warner, Nathaniel R.; Blotevogel, Jens; Borch, Thomas
Abstract : Produced water (PW) is the largest waste stream associated with oil and gas (O&G) operations and contains petroleum hydrocarbons, heavy metals, salts, naturally occurring radioactive materials and any remaining chemical additives. Abstract : Produced water (PW) is the largest waste stream associated with oil and gas (O&G) operations and contains petroleum hydrocarbons, heavy metals, salts, naturally occurring radioactive materials and any remaining chemical additives. In some areas in Wyoming, constructed wetlands (CWs) are used to polish PW downstream of National Pollutant Discharge Elimination System (NPDES) PW release points. In recent years, there has been increased interest in finding lower cost options, such as CWs, for PW treatment. The goal of this study was to understand the efficacy of removal and environmental fate of O&G organic chemical additives in CW systems used to treat PW released for agricultural beneficial reuse. To achieve this goal, we analyzed water and sediment samples for organic O&G chemical additives and conducted 16S rRNA gene sequencing for microbial community characterization on three such systems in Wyoming, USA. Three surfactants (polyethylene glycols, polypropylene glycols, and nonylphenol ethoxylates) and one biocide (alkyldimethylammonium chloride) were detected in all three PW discharges and >94% removal of all species from PW was achieved after treatment in two CWs in series. These O&G extraction additives were detected in all sediment samples collected downstream of PW discharges. Chemical and microbial analyses indicated that sorption and biodegradation were the main attenuation mechanisms for these species. Additionally, all three discharges showed a trend of increasingly diverse, but similar, microbial communities with greater distance from NPDES PW discharge points. Results of this study can be used to inform design and management of constructed wetlands for produced water treatment.